2011
DOI: 10.1164/rccm.201009-1452oc
|View full text |Cite
|
Sign up to set email alerts
|

Airway Fibroblasts in Asthma Manifest an Invasive Phenotype

Abstract: Rationale: Invasive cell phenotypes have been demonstrated in malignant transformation, but not in other diseases, such as asthma. Cellular invasiveness is thought to be mediated by transforming growth factor (TGF)-b1 and matrix metalloproteinases (MMPs). IL-13 is a key T H 2 cytokine that directs many features of airway remodeling through TGF-b1 and MMPs. Objectives: We hypothesized that, in human asthma, IL-13 stimulates increased airway fibroblast invasiveness via TGF-b1 and MMPs in asthma compared with nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 42 publications
(38 reference statements)
1
44
0
4
Order By: Relevance
“…Fibroblast invasiveness may contribute to other fibrotic conditions as well, such as remodeling of the airways in asthma and remodeling of the joints in rheumatoid arthritis. Airway fibroblasts from patients with asthma are more invasive than those from control subjects (27), and fibroblast-like Figure 6. BAL from patients with idiopathic pulmonary fibrosis (IPF) induces non-cell-autonomous invasion of lung fibroblasts from patients with IPF.…”
Section: Discussionmentioning
confidence: 99%
“…Fibroblast invasiveness may contribute to other fibrotic conditions as well, such as remodeling of the airways in asthma and remodeling of the joints in rheumatoid arthritis. Airway fibroblasts from patients with asthma are more invasive than those from control subjects (27), and fibroblast-like Figure 6. BAL from patients with idiopathic pulmonary fibrosis (IPF) induces non-cell-autonomous invasion of lung fibroblasts from patients with IPF.…”
Section: Discussionmentioning
confidence: 99%
“…IL-13 indirectly causes asthmatic airway fibroblasts to secrete collagen I via MMP-2 released TGF-b1 [120]. IL-13 also causes bronchoscopy-derived primary asthmatic lung fibroblasts to migrate through matrigel in a TGF-b-dependent fashion [121]. IL-13 induces bronchial biopsy-derived primary lung epithelial cells to release TGF-b2 in a corticosteroid-insensitive fashion [122].…”
Section: Fibrosismentioning
confidence: 99%
“…We hypothesize that airways collapsibility associated with reduced airway elastin increases susceptibility to not only methacholine but also to other mediators known to cause bronchoconstriction, such as allergens and airway irritants. Furthermore, we have previously shown that IL-13-induced airway fibroblast invasion in asthma was inversely associated with methacholine PC 20 (12). Taken together, these data suggest that airway fibroblasts isolated from subjects with mild asthma exhibiting the most severe AHR are more susceptible to IL-13-directed signaling than those with less severe AHR, associating AHR with airway remodeling as manifested by airway wall thickening and stiffening due to increased subepithelial fibrosis and reduced elastin gene expression.…”
Section: Discussionmentioning
confidence: 64%
“…These cells, along with airway smooth muscle cells, produce elastin, alter lung architecture after injury, stimulate inflammation, and respond to cytokines relevant to asthma such as IL-4, IL-13, and transforming growth factor-b1 (10)(11)(12)(13). Specific fibroblast responses include mitogen-stimulated proliferation, invasion, and collagen production (12)(13)(14).…”
mentioning
confidence: 99%
See 1 more Smart Citation